2015
DOI: 10.1007/s10646-015-1552-3
|View full text |Cite
|
Sign up to set email alerts
|

Real-time toxicity and metabolic activity tracking of human cells exposed to Escherichia coli O157:H7 in a mixed consortia

Abstract: Escherichia coli O157:H7 is a significant human pathogen that is continually responsible for sickness, and even death, on a worldwide scale. While the pathology of E. coli O157:H7 infection has been well studied, the effect of it’s multiple resulting cytotoxic mechanisms on host metabolic activity has not been well characterized. To develop a more thorough understanding of these effects, several bioluminescence assays were evaluated for their ability to track both toxicity and host metabolic activity levels in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…The use of autobioluminescence as a metabolic activity reporter system has been used in a variety of cell types and applications [ 7 , 17 , 18 , 19 , 20 , 21 , 22 ], but has not been well-investigated for co-culture-based systems such as those used for drug discovery. In this work, we evaluated if this system could be used in this application, and if doing so could provide economical or logistical advantages relative to existing systems.…”
Section: Discussionmentioning
confidence: 99%
“…The use of autobioluminescence as a metabolic activity reporter system has been used in a variety of cell types and applications [ 7 , 17 , 18 , 19 , 20 , 21 , 22 ], but has not been well-investigated for co-culture-based systems such as those used for drug discovery. In this work, we evaluated if this system could be used in this application, and if doing so could provide economical or logistical advantages relative to existing systems.…”
Section: Discussionmentioning
confidence: 99%
“…This approach, which substituted viral 2A elements in place of the previously employed IRES elements, allowed the full autobioluminescent DNA cassette to be manipulated as a single gene and significantly increased the signal output level to the point where it could be detected from the low numbers of cells that are commonly used in high throughput screening applications. Using the new expression format, Xu and her colleagues were able to demonstrate the use of autobioluminescent reporters for tracking cellular metabolic dynamics, population sizes, and promoter activation events, finally demonstrating the use of autobioluminescence for the same applications as traditional bioluminescent reporter systems [19,20].…”
Section: History Of Autobioluminescent Cellular Model Developmentmentioning
confidence: 99%
“…Functionally, this means that autobioluminescent systems can be utilized to monitor the metabolic activity or population size dynamics of specific community members in heterogeneous cocultures. This ability was recently investigated using cocultures of autobioluminescent HEK293 cells and virulent Escherichia coli O157:H7 to study the metabolic effects of bacterial infection and better understand the mechanism and timing of E. coli O157:H7 infection to improve treatment options for exposed patients [20].…”
Section: Advantages Of Autobioluminescent Cellular Models For Assayinmentioning
confidence: 99%
“…E. coli O157:H7 is a significant human pathogen that is continually responsible for sickness and even death on a worldwide scale. Xu et al (2015b) reported that a critical bacterial infection level (i.e., 5-10 9 10 5 ) must be reached prior to the onset of cytotoxic effects of E. coli O157:H7. They found that cells displaying infection-mediated metabolic activity reductions could recover to wild type metabolic activity levels if the infecting bacteria were removed prior to cell death.…”
Section: Toxic Effect During Disinfection Processmentioning
confidence: 99%